2021
DOI: 10.1371/journal.pone.0252687
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of SARS-CoV-2 virus in saliva using a guanidium based transport medium suitable for RT-PCR diagnostic assays

Abstract: Background Upper respiratory samples used to test for SARS-CoV-2 virus may be infectious and present a hazard during transport and testing. A buffer with the ability to inactivate SARS-CoV-2 at the time of sample collection could simplify and expand testing for COVID-19 to non-conventional settings. Methods We evaluated a guanidium thiocyanate-based buffer, eNAT™ (Copan) as a possible transport and inactivation medium for downstream Reverse Transcriptase-Polymerase Chain Reaction (RT-PCR) testing to detect S… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
13
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 23 publications
4
13
0
Order By: Relevance
“…This is a strong chaotropic agent with the ability to deactivate viruses and preserve nucleic acids by disabling the action of nucleases and protein structures 21 . The use of this viral stabilizing and inactivating agent has been widely used in the study of several viruses 22,23 including SARS‐CoV‐2 for their detection and diagnosis during the pandemic 12,24,25 . For example, Carvalho et al 26 analyzed NPSs kept in the medium with guanidine salts, obtaining Cq values like those reported in our current study.…”
Section: Discussionsupporting
confidence: 73%
“…This is a strong chaotropic agent with the ability to deactivate viruses and preserve nucleic acids by disabling the action of nucleases and protein structures 21 . The use of this viral stabilizing and inactivating agent has been widely used in the study of several viruses 22,23 including SARS‐CoV‐2 for their detection and diagnosis during the pandemic 12,24,25 . For example, Carvalho et al 26 analyzed NPSs kept in the medium with guanidine salts, obtaining Cq values like those reported in our current study.…”
Section: Discussionsupporting
confidence: 73%
“…Thus, during the COVID-19 pandemic, the FDA allowed laboratories to consider the use of alternative transport media [ 12 ]. Among these, the guanidine thiocyanate-based eNAT™ medium reportedly inactivates SARS-CoV-2 and stabilizes its nucleic acid [ 19 , 20 , 30 ]. In this study, we demonstrated the efficacy of GeneTM (another guanidine thiocyanate-based medium) by comparing it with eNAT™, using PBS as a control.…”
Section: Discussionmentioning
confidence: 99%
“…There are studies on guanidine thiocyanate-based media that are suitable for virus inactivation and RT-qPCR detection assays [ 19 ]. eNAT™ (Copan, Brescia, Italy) is a guanidine thiocyanate-based medium that can help nucleic acids remain stable for a long period and is suitable for sample collection and transport [ 20 ]. Similarly, GeneTM is a guanidine thiocyanate-based medium that is suitable for collecting nasal (nasopharyngeal) and oral (oropharyngeal or salivary) samples for respiratory infection testing; it can also be used for the transportation and preservation of samples for COVID-19 testing.…”
Section: Introductionmentioning
confidence: 99%
“…Guanidinium thiocyanate or guanidinium hydrochloride has shown to inactivate SARS-CoV-2 and can be used for RT-PCR applications [ 52 54 ] since inactivation reagents were effective at reducing viral titers [ 55 ]. It was suggested to be used as part of SARS-CoV-2 NAAT at high-risk locations (schools, workplaces, prisons, skilled nursing facilities, homeless shelters, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…It was suggested to be used as part of SARS-CoV-2 NAAT at high-risk locations (schools, workplaces, prisons, skilled nursing facilities, homeless shelters, etc.) [ 52 ]. In this research, VITPAD®, a guanidine-based inactivation transport media (ITM) formulated to maintain the RNA quality of SARS-CoV-2 during transportation without cold chains, was evaluated.…”
Section: Introductionmentioning
confidence: 99%